Evaluating the effects of hypoxia and taper on expression of Pulmonary Bax and Bcl2 apoptotic proteins - Mehdi Yadegari; Simin Riahy; Shadmehr Mirdar; Gholamreza Hamidiyan; Parinaz Mosadegh; Fariba Yahyavi (Fasa University of Medical Sciences, 2018)
Background & Objective: Due to The limitation of research literature, related to the effect of exercise training with different intensity, Along with Hypoxia Stress on Pulmonary Apoptosis, The purpose of this study was to investigate the effects of hypoxia and taper on expression of Bax and Bcl2 apoptotic proteins of lung.   Materials & Methods: In this experimental study Twenty-four rats (4-week old, 72±8 gr) were divided accidentally to control and training groups. The samples after 6 weeks anaerobic exercise training, were exposed to Environment hypoxia and lived three weeks over there. Another group Concurrent with exposure to hypoxic environment, implementation Taper (30% reduction in exercise intensity) technique. In lung tissue, the expression of Bax and Bcl2 was studied by the immunohistochemical methods. One-way Anova was performed to analyze data. P≤0.05 was considered statistically significant. Results:Expression of Bcl2 protein in trained rats and exposed to hypoxic stress was increased And reduced after a 3-week use of the taper(P>0.05). Expression of Bax protein in trained rats and exposed to hypoxic stress was increased (P≤0.05), and reduced after a 3-week use of the taper (P>0.05).   Conclusion: It seems that, Medium hypoxia is able to apply Apoptotic effects in lung of rats that underwent intensive exercise and likely the use of intensity taper reduces these effects.